Wound Healing activity of Leaves & roots of Pavetta Indica Linn of by using different extracts: Wound Healing activity of Leaves & roots of Pavetta Indica Linn of by using different extracts - Prasad, Satkar (International Journal of Pharmaceutical & Biological Archive, 2018)
Pavetta indica, which is known as kankara in Hindi, is widely distributed in the greater part of India. P. indica is a traditional medicinal plant having for various diseases. Objective: The aim of the present study to evaluate the wound healing activity on different extracts (petroleum ether, chloroform, and methanol) of leaves and roots of P. indica Linn. in albino rats using excision and incision wound models. Materials and Methods: The excision and incision wounds were inflicted on eight groups, each group having six albino rates and divided one group for control, six groups for test, and one group for standard treated with povidone iodine ointment. The parameter in excision observed was wound contraction and incision model was tensile strength. Result: It was noted that the effect produced by the methanolic extract of P. indica ointment showed a significant healing in both wound models. The studies indicate that the root extracts of plant have more potent healing as compared to leaf extracts. Conclusion: The results further suggest that P. indica facilitates healing by increasing the rate and extent of wound closure and increased tensile strength in wounds subject to healing.